Poly-γ-glutamic acid coupled Pseudomonas putida cells surface-displaying metallothioneins: composited copper(ii) biosorption and inducible flocculation in aqueous solution. Issue 30 (28th March 2017) - Hu, Penggao; Zhang, Zhongna; Shen, Fei; Yu, Xun; Li, Mingshun; Ni, Hong; Li, Lin
Abstract : Schematic illustration of the preparation, biosorption, and induced flocculation of the biocomposite MB546-PGA. Abstract : Poly-γ-glutamic acid (γ-PGA) is a biodegradable macromolecular polymer that is capable of adsorbing heavy metal ions through its side chains. In this study, a new biocomposite biosorbent that incorporates Cu 2+ adsorption and recovery from aqueous solutions was developed through immobilization of a glutamine-binding protein GlnBP and cyanobacterial metallothionein SmtA onto the surface of Pseudomonas putida cells using an InaQ-N protein anchor, followed by coupling the cells with side chain-activated γ-PGA. The surface localization of the fusion protein (InaQ)2 –GlnBP–(SmtA)2 was confirmed by SDS-PAGE/Western blot, immunofluorescence microscopy and fluorescence-activated cell sorting assays. The engineered biocomposite MB546-PGA was capable of Cu 2+ adsorption across a pH range of 3.5–5.5 and a relatively broad temperature range of 20–60 °C, with a maximum adsorption capacity for Cu 2+ of 145.99 mg g −1 . The pseudo-second-order equation was applicable to the sorption data. Moreover, MB546-PGA exhibited an inducible flocculation capability following Cu 2+ adsorption. The infrared spectroscopy data showed that the hydroxyl and amino groups of MB546-PGA were involved in Cu 2+ adsorption, and γ-PGA likely bound to the cells through its carbonyl and amino groups. Given the features of the high capacity of Cu 2+ adsorption and the easily inducible flocculation, the developed biosorbent shows potential for use in the remediation and purification of polluted or waste waters.